A PID de-tuned method for multivariable systems, applied for HVAC plant - Ghazali A.B. (Institute of Physics Publishing, 2023)
Energy utilization; Multivariable systems; Three term control systems; Building energy management systems; Controller performance; Multi variables; PID controllers; PID parameters; Squared errors; Steady-state condition; Total energy consumption; Energy management systems